PENINGKATAN CITRA MELALUI PROGRAM POLISI SAHABAT PETANI DALAM PEMBERITAAN MEDIA ONLINE - Bafiki Putra, Al Bhaihaqi; Lailiyah, Fatihatul; Ramadhani, Rakhmad Saiful (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2024)
In recent years, there have been indications of public doubt regarding the role and function of the Police as law enforcers after many cases involving internal police that have attracted public or community attention, starting from the case of Inspector General of Police Ferdi Sambo who shot his subordinates, the drug case involving former East Java Police Chief Inspector General of Police Teddy Minahasa, and several other cases. This study aims to analyze the critical discourse of news about the "Police Friend of Farmers" program in online media. The method used is a descriptive qualitative approach with Norman Fairclough's critical discourse analysis model. This approach aims to understand the reality or existing phenomena. This study utilizes Fairclough's critical discourse analysis which includes three-dimensional analysis: textual analysis, discourse practice analysis, and sociocultural practice analysis. The results of the analysis show that news about the "Police Friend of Farmers" program shows a certain agenda from the police, which is aimed at changing public perception about the Police. The news highlighted the role of the police in creating the innovation of PSB organic fertilizer as a solution to the scarcity of fertilizer, but also showed a slight deficiency in the absence of a comment column in the news, in online media so that it is not possible to know the positive or negative responses received.